Pre-emergent herbicides on peach orchard - Pereira, José Francisco Martins; Medeiros, Antonio Roberto Marchese de; Bassols, Maria do Carmo (Pesquisa Agropecuaria Brasileira, 2014)
Three pre-emergent herbicides were tested, at two different concentrations, with the aim to keep the peach orchards free of weeds during the vegetative cicle. The experiment was conducted near Cascata, Rio Grande do Sul, Brazil, in a three-year-old peach orchard, cv. Princesa, a fresh marketing cultivar. The best treatments were Diuron at 1.6 kg A.I./ha and Simazine at 2.2 kg A.I./ha. However, the control of weeds was better in all the herbicide treated plots than in the ones hoed. There were no significant differences in seed germination in the different soil sample, as compared to the controls. There were no significant differences among treatments regarding fruit production, fruit size and stem development. The bioassay was made using seeds of canary grass and wild chicory and the results showed no residues of herbicides in the soil, 310 and 320 days after their application.